2019
DOI: 10.1002/ps.5322
|View full text |Cite
|
Sign up to set email alerts
|

From synthetic control to natural products: a focus on N‐heterocycles

Abstract: Natural products containing a N‐heterocycle motif are widespread in nature and medicinal plants, in particular, have proved to be a source of almost unlimited N‐derived structures with high molecular diversity. Because of their intrinsic potential for use in both biomedical and agricultural applications, there is a general need for new compounds and for the synthesis of ‘natural‐inspired’ analogues. Importantly, transition of a natural product from discovery to a ‘market lead’ is associated with an increasingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 119 publications
(194 reference statements)
0
23
0
Order By: Relevance
“…H eterocyclizations are powerful tools for the synthesis of five-membered heterocycles 1−4 that are often found in natural products 5,6 and synthetic pharmaceuticals 7−9 and widely used in material science and organic synthesis. 10−17 Recent studies revealed that oxidative heterocyclizations 18−21 could evoke novel and useful catalytic transformations, which otherwise are difficult to achieve.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…H eterocyclizations are powerful tools for the synthesis of five-membered heterocycles 1−4 that are often found in natural products 5,6 and synthetic pharmaceuticals 7−9 and widely used in material science and organic synthesis. 10−17 Recent studies revealed that oxidative heterocyclizations 18−21 could evoke novel and useful catalytic transformations, which otherwise are difficult to achieve.…”
mentioning
confidence: 99%
“…Heterocyclizations are powerful tools for the synthesis of five-membered heterocycles that are often found in natural products , and synthetic pharmaceuticals and widely used in material science and organic synthesis. Recent studies revealed that oxidative heterocyclizations could evoke novel and useful catalytic transformations, which otherwise are difficult to achieve. For example, the cyclization of ketene dithioacetals, a kind of electron-rich olefin, under electrochemical conditions afforded the cyclic amino acid derivatives (Scheme a, X = NH) .…”
mentioning
confidence: 99%
“…Azaheterocycles are highly abundant structural elements in natural products, drugs, and other bioactive molecules (Figure 1 ). 9 10 11 As a consequence, the synthesis of functionalized azaheterocycles remains a highlighted topic in medicinal chemistry and there is a constant need to develop novel methods. 5,11…”
mentioning
confidence: 99%
“…[6][7][8] Scheme 1 General mechanisms for ring-rearrangement metathesis Azaheterocycles are highly abundant structural elements in natural products, drugs, and other bioactive molecules (Figure 1). [9][10][11] As a consequence, the synthesis of functionalized azaheterocycles remains a highlighted topic in medicinal chemistry and there is a constant need to develop novel methods. 5,11 Azaheterocyclic -amino acids are an interesting subgroup of this compound family.…”
mentioning
confidence: 99%
“…The use of biopesticides in underdeveloped countries was reviewed by Srinivasan et al . There was a more focused review on natural N ‐heterocyclic compounds as leads for pesticides . The use of strigolactones for parasitic weed management and the use of alleopathy for weed management in general were updated .…”
mentioning
confidence: 99%